Condition, prolonged swimming performance and muscle metabolic capacities of cod Gadus morhua - Martínez, M.; Guderley, H.; Dutil, J.-D.; Winger, P. D.; He, P.; Walsh, S. J. (Journal of Experimental Biology, 2003)
This study evaluated the link between swimming endurance and condition of Atlantic cod Gadus morhua that had been fed or starved during the 16 weeks preceding the tests, and assessed whether muscle metabolic capacities explain such links. The condition factor [(somatic mass × fork length-3)×100] of starved cod was 0.54±0.1 whereas that of fed cod was 0.81±0.1. In white and red muscle, we measured four glycolytic enzymes: phosphofructokinase (PFK), pyruvate kinase (PK), creatine kinase (CK) and lactate dehydrogenase (LDH), two mitochondrial enzymes: cytochrome c oxidase (CCO) and citrate synthase (CS), a biosynthetic enzyme, nucleoside diphosphate kinase (NDPK), glycogen and protein levels and water content. Muscle samples were taken at three positions along the length of the fish; starvation affected the metabolic capacities of white muscle more than those of red muscle. The levels of glycolytic enzymes and glycogen changed more in white than red muscle during starvation. Both in fed and starved cod, muscle metabolic capacities varied with position along the fish; starvation reduced this longitudinal variation more in white than red muscle. In white muscle of fed cod, the glycolytic enzyme levels increased from head to tail, while in starved cod this longitudinal variation disappeared. In red muscle mitochondrial enzyme levels were highest in the caudal sample, but fewer differences were found for glycolytic enzymes. Swimming endurance was markedly affected by fish condition, with starved fish swimming only 30% of the time (and distance) of fed fish. This endurance was closely linked with the number of burst—coast movements during the test and the activity of CCO and LDH in white muscle. The number of burst—coast movements was significantly linked with condition factor and PFK activity in caudal red muscle and gill arch mass. Our data indicated that cod use both glycolytic and oxidative capacities to support endurance swimming. Furthermore, swimming endurance is linked with the metabolic capacities of red and ...